Hypertension Treatment and Concern About Falling: Baseline Data from the Systolic Blood Pressure Intervention Trial. Issue 11 (19th September 2016) - Berlowitz, Dan R.; Breaux‐Shropshire, Tonya; Foy, Capri G.; Gren, Lisa H.; Kazis, Lewis; Lerner, Alan J.; Newman, Jill C.; Powell, James R.; Riley, William T.; Rosman, Robert; Wadley, Virginia G.; Williams, Julie A.; et al.
Abstract : Objectives: To determine the extent of concern about falling in older adults with hypertension, whether lower blood pressure (BP) and greater use of antihypertensive medications are associated with greater concern about falling, and whether lower BP has a greater effect on concern about falling in older and more functionally impaired individuals. Design: Secondary analysis involving cross‐sectional study of baseline characteristics of participants enrolled in the Systolic Blood Pressure Intervention Trial (SPRINT). Setting: Approximately 100 outpatient sites. Participants: SPRINT enrollees aged 50 and older (mean age 69) diagnosed with hypertension (N = 2, 299). Measurements: Concern about falling was determined using the shortened version of the Falls Efficacy Scale International as measured at the baseline examination. Results: Mild concern about falling was present in 29.3% of participants and moderate to severe concern in 17.9%. Neither low BP (systolic BP<120 mmHg, diastolic BP <70 mmHg) nor orthostatic hypotension was associated with concern about falling ( P > .10). Participants with moderate to severe concern about falling were taking significantly more antihypertensive medications than those with mild or no concern. After adjusting for baseline characteristics, no associations were evident between BP, medications, and concern about falling. Results were similar in older and younger participants; interactions between BP and age and functional status were not significantly associated with concern about falling. Conclusion: Although concern about falling is common in older adults with hypertension, it was not found to be associated with low BP or use of more antihypertensive medications in baseline data from SPRINT.